2010
DOI: 10.1136/emj.2010.094219
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic application of ultrasound in the management of patients in the prehospital setting: a review of the literature

Abstract: The theoretical concept that paramedic-initiated prehospital ultrasound may be of benefit in the management of critically ill patients is not without logical conceptual reason. Studies to date have demonstrated that with the right education and mentorship, some paramedic groups are able to obtain ultrasound images of sufficient quality to positively identify catastrophic pathologies found in critically ill patients. More research is required to demonstrate that these findings are transferable to the infrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…It is a noninvasive, quick and easy examination that can provide ongoing information about a patient's condition and is well established in the European system of physician-led prehospital care [7]. Critically, it can provide information related to a reversible aetiology for CA or identify the presence of subtle cardiac function when a pulse is not detected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a noninvasive, quick and easy examination that can provide ongoing information about a patient's condition and is well established in the European system of physician-led prehospital care [7]. Critically, it can provide information related to a reversible aetiology for CA or identify the presence of subtle cardiac function when a pulse is not detected.…”
Section: Introductionmentioning
confidence: 99%
“…It is a user-dependent technique and relies upon an operator's ability to capture and interpret images [7]. In the context of a CA, ultrasound has a very narrow window of use and must be performed in the 10-s pulse check to ensure that chest compressions are not interrupted [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training in the use of PHUS has been considered a limitation [19] and is considered a challenge by previous reviews [47,52,53]. Studies have found PHUS training to be feasible both with physicians [54,55] and non-physicians [53,[56][57][58][59][60].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Studies have found PHUS training to be feasible both with physicians [54,55] and non-physicians [53,[56][57][58][59][60]. Nonphysician use of PHUS in changing patient management has not been studied.…”
Section: Summary Of Evidencementioning
confidence: 99%